1997
DOI: 10.1159/000190320
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Three Xanthine Derivatives (Theophylline, Caffeine and Pentoxifylline) against the Cyclosporin A-lnduced Glomerular Contraction in Isolated Glomeruli and Cultured Mesangial Cells

Abstract: Cyclosporin A (CyA), an immunosuppressive agent, induces in vivo a severe nephrotoxicity with large decrease in renal hemodynamics correlated with in vitro glomerular contraction. The aim of this study is to show the ability of three xanthine derivatives, caffeine, theophylline and pentoxifylline, to diminish the CyA-induced in vitro glomerular contraction. The use of isolated glomeruli and cultured rat mesangial cells permits us to evaluate by quantitative and qualitative morphometric analysis the contraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In early studies in rats, theophylline failed to ameliorate cyclosporine-induced renal vasoconstriction indicating that it was not caused by adenosine (Churchill et al 1990). Subsequently however, caffeine, theophylline, and pentoxifylline were observed to reduce the acute contractile response of isolated glomeruli and mesangial cells in culture to cyclosporine (Potier et al 1997). Furthermore, the acute reduction of GFR and renal blood flow caused in rats by a single dose of tacrolimus was completely reversed by theophylline given 1 hour after the drug (McLaughlin et al 2003a).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%
“…In early studies in rats, theophylline failed to ameliorate cyclosporine-induced renal vasoconstriction indicating that it was not caused by adenosine (Churchill et al 1990). Subsequently however, caffeine, theophylline, and pentoxifylline were observed to reduce the acute contractile response of isolated glomeruli and mesangial cells in culture to cyclosporine (Potier et al 1997). Furthermore, the acute reduction of GFR and renal blood flow caused in rats by a single dose of tacrolimus was completely reversed by theophylline given 1 hour after the drug (McLaughlin et al 2003a).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%
“…Phosphodiesterase inhibition typically requires THEO serum concentrations of greater than 10 mg/dl, levels that were achieved in this study for at least part of each day. However, in isolated glomeruli cyclic nucleotide analogues, while able to induce excessive production of cyclic AMP, did not show the same protective effect on cyclosporine induced vasoconstriction as did THEO [28]. Moreover, enprofylline, a phosphodiesterase inhibitor lacking in adenosine inhibition, had no effect on cisplatin toxicity in rabbits [14].…”
Section: Resultsmentioning
confidence: 99%
“…In isolated glomeruli exposed to cyclosporine, induction of high concentrations of cyclic adenosine monophosphate by several cyclic nucleotide analogs had minimal effect on vasoconstriction when compared with the effect of THEO itself (15). Albornoz et al (21) demonstrated that pentoxifylline preserved renal function as measured by renal plasma flow and GFR after a 10-day course of cyclosporine.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Hwang et al (14) demonstrated that TAC, but not cyclosporine, promotes adenosine release from cultured endothelial cells. In an in vitro model of isolated glomeruli and cultured rat mesangial cells, cyclosporine-induced vasoconstriction was prevented by xanthine derivatives with adenosine receptor antagonist activity (15).…”
mentioning
confidence: 99%